2021
DOI: 10.1038/s41598-021-87250-7
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion and transformation of solution combustion synthesized Co, Ni and CoNi nanoparticles in synthetic freshwater with and without natural organic matter

Abstract: Pure metallic Co, Ni, and their bimetallic compositions of Co3Ni, CoNi, and CoNi3 nanomaterials were prepared by solution combustion synthesis. Microstructure, phase composition, and crystalline structure of these nanoparticles (NPs) were characterized along with studies of their corrosion and dissolution properties in synthetic freshwater with and without natural organic matter (NOM). The nanomaterials consisted of aggregates of fine NPs (3–30 nm) of almost pure metallic and bimetallic crystal phases with a t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…The XPS results showed that before the catalysis, the Co concentration on the outermost surface of the SGCS alloy catalysts was higher than that of Ni, even when the stoichiometric ratio of the constituents was kept in a larger volume. A similar trend has been observed in other studies [ 42 ]. However, after the catalysis, the amount of Ni on the surface increased ( Table S1 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The XPS results showed that before the catalysis, the Co concentration on the outermost surface of the SGCS alloy catalysts was higher than that of Ni, even when the stoichiometric ratio of the constituents was kept in a larger volume. A similar trend has been observed in other studies [ 42 ]. However, after the catalysis, the amount of Ni on the surface increased ( Table S1 ).…”
Section: Discussionsupporting
confidence: 92%
“…Sol-gel combustion synthesis (SGCS) is a unique approach for tailoring the morphology of a material, and allows the fabrication of metallic foams with controlled pore-size distribution [ 42 , 43 , 44 , 45 ]. In this work, we studied the synergetic effect of Co-Ni bonds in bulk Co-Ni alloys on the CO 2 conversion reaction run on sponge-like structural metal catalysts fabricated by SGCS.…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology-based nanomaterials (NMs) synthesis has attracted the attention of researchers in the modern scientific world compared to that of bulk materials. 1 Improvement in the synthesis approach, along with its crucial outlooks, is the current worldwide consideration, ordinarily, for industrially-scalable applications. Understanding the process from precursor decomposition to nanocrystal formation using advanced instruments allows for controlling the materials' size, morphology, and crystallinity.…”
Section: Introductionmentioning
confidence: 99%
“…The SG-SCS follows 1) colloidal/sol formations, 2) gel formation by evaporating the water molecules, 3) locally activated combustion reaction (Khort et al, 2021;Novitskaya et al, 2021), 4) propagation along the rest of the media, and 5) finally, the quenching of the reaction by the evolution of gases. Of course, the by-product may further react to the reducing gases/ atmosphere and result in a metal reduction.…”
Section: Introductionmentioning
confidence: 99%